Study of Molecular Interactions in Binary Mixtures of Diethyl Carbonate + Benzene Derivatives at Different Temperatures - Narendra, K.; Sudhamsa, B.; Babu, M. Sarath; Krishna, T.S. (Journal of Applied Solution Chemistry and Modeling, 2015)
Investigation on the molecular interactions between binary mixtures containing diethyl carbonate in combination with nitrobenzene, chlorobenzene and aniline is presented. Ultrasonic velocity and density values were determined for the individual components as well as binary mixtures of the above benzene derivatives with diethyl carbonate at temperatures (293.15, 298.15, 303.15, 308.15, 313.15, 318.15 and 323.15) K over the entire composition range. Further, adiabatic compressibility and acoustic impedance values were calculated using the experimental results. In addition to these parameters, the excess parameters like excess adiabatic compressibility, excess acoustic impedance and deviation in ultrasonic velocity were also obtained. Based on all these results, molecular interactions among the selected components were discussed.